Comparing image quality of coronary CT angiography with and without ECG-gating in wide-detector CT - Kun Wang; Yueqiao Zhang; Bin Chen; Hong Ren (Frontiers in Cardiovascular Medicine)
ObjectiveTo compare the image quality, radiation dose, and examination time between non-electrocardiogram (ECG)-gated coronary CT angiography (ECG-less CCTA) and conventional ECG-gated CCTA using wide-detector CT, and validate its clinical applicability.MethodsIn this prospective study, 109 patients with suspected coronary artery disease were divided into ECG-less (Group A, n = 59) and ECG-gated (Group B, n = 50) groups. Objective metrics (CT attenuation, noise, SNR, CNR), subjective image quality (4-point scale), and examination time were analyzed. Diagnostic performance (sensitivity, specificity) was evaluated against invasive coronary angiography (ICA). A modified ECG-less protocol (Group A2, n = 30) was implemented to optimize radiation dose. Plaque characterization agreement was assessed using Cohen’s κ.ResultsThe ECG-less group demonstrated higher radiation dose (2.83 ± 0.93 vs. 1.90 ± 1.41 mSv, p < 0.001) but significantly shorter examination time (225.03 ± 33.37 vs. 330.06 ± 56.35 s, p < 0.001). The modified ECG-less protocol reduced the effective dose by 28% (2.03 ± 0.75 mSv, p < 0.001 vs. Group A), achieving statistical comparability to the conventional group (p = 0.62). Subjective image scores (4-point scale) and SNR/CNR showed no significant differences between groups (p > 0.05). ECG-less CCTA achieved per-segment sensitivity/specificity of 93.3%/97.5% and per-patient 94.4%/50% for detecting ≥50% stenosis. Plaque characterization exhibited high agreement (calcified: κ = 0.82; non-calcified: κ = 0.78; mixed: κ = 0.75).ConclusionECG-less CCTA provides comparable image quality and diagnostic accuracy to conventional ECG-gated CCTA while significantly reducing examination time. This technique is applicable in emergency scenarios where ECG lead placement is unfeasible (e.g., severe trauma, unreliable ECG signals).